Duplications of an iron–sulphur tripeptide leads to the formation of a protoferredoxin. Issue 92 (28th October 2016) - Scintilla, Simone; Bonfio, Claudia; Belmonte, Luca; Forlin, Michele; Rossetto, Daniele; Li, Jingwei; Cowan, James A.; Galliani, Angela; Arnesano, Fabio; Assfalg, Michael; Mansy, Sheref S.
Abstract : Based on UV-Vis, NMR, and EPR spectroscopies and DFT and molecular dynamics calculations, a model prebiotic [2Fe–2S] tripeptide was shown to accept and donate electrons. Abstract : Based on UV-Vis, NMR, and EPR spectroscopies and DFT and molecular dynamics calculations, a model prebiotic [2Fe–2S] tripeptide was shown to accept and donate electrons. Duplications of the tripeptide sequence led to a protoferredoxin with increased stability. Duplications of primitive peptides may have contributed to the formation of contemporary ferredoxins.